CONFUSION OF REAL SITE IMPLEMENTATION OF VSD UTILIZATION ON WATER PUMP OF A CHILLER PLANT SYSTEM IN OFFICE BUILDING JAKARTA - Marhaendra Natawibawa (LPSDI Bina Patria, 2024)
The utilization of VSD in centralized air conditioning systems has been applied for years for efficiency purposes. However, found in real implementation has not been really applied as its function yet. This paper will present real site implementation of applying VSD on regulating the motor speed of chilled water pump as its function [1] to control the chilled water flow rate [2] go into the evaporator to let the chiller work as correspond on cooling demand at the actual load level and at its necessary power input. By analyzing some related parameters such as temperature, water pressure and amperes measured and observed to be the raw data then they will show the working performance of chiller impact on energy consumed to be evaluated on its efficiency impact. Found the real implementation at this site the VSD does not look like varying the speed of motor pump as usually applied but more by being set at certain frequency such as 32 Hz. Then mostly the chiller cannot be run as high as cooling demand as running at only about 50-60% as lower chilled water flow rate flowing into the evaporator. Other than that it looks efficiency of refrigeration effect on handling the building load is not good enough as mentioned in catalogue/reference with difficulties on reaching the target chilled water leaving temperature.